Extremely small and incredibly close: Gut microbes as modulators of inflammation and targets for therapeutic intervention - Piazzesi, Antonia; Putignani, Lorenza (Frontiers in Microbiology, 2022)
Chronic inflammation is a hallmark for a variety of disorders, and is at least partially responsible for disease progression and poor patient health. In recent years, the microbiota inhabiting the human gut has been associated with not only intestinal inflammatory diseases, but also those that affect the brain, liver, lungs and joints. Despite a strong correlation between specific microbial signatures and inflammation, whether or not these microbes are disease markers or disease drivers is still a matter of debate. In this review, we discuss what is known about the molecular mechanisms by which the gut microbiota can modulate inflammation, both in the intestine and beyond. We identify the current gaps in our knowledge of biological mechanism, discuss how these gaps have likely contributed to the uncertain outcome of fecal microbiota transplantation and probiotic clinical trials, and suggest how both mechanistic insight and -omics-based approaches can better inform study design and therapeutic intervention.